Implementasi Manajemen Keuangan di SMA Labschool UNESA - Valentiara, Nadhea Kusuma; Hernowo, Ayu Angela Rahma; Siahaan, Dborah Graciana; Rahmawati, Febiana Veliza; Nengrum, Felis Tria; Wulandari, Ayu (Lembaga Yasin AlSys, 2024)
Financial management is a science and art that discusses, examines, and analyzes how financial managers use all company resources to find, manage, and allocate funds. Financial management or commonly called learning can be explained as all company activities related to efforts to obtain company funds at low cost and use and allocate these funds efficiently. The purpose of the article is to describe how to implement financial management at Labschool Unesa High School. In this article the method used is qualitative by conducting interviews, observations and documentation studies. Labschool Unesa High Schoolhas good financial management by providing quality education to students for the success of the school in achieving its goals. In addition, this article also discusses financial management, how to overcome finances in urgent circumstances, budget plans, and so on related to this school.